Fit for Office? The Perception of Female and Male Politicians by Dutch Voters - van Dijk, Rozemarijn E.; van Holsteyn, Joop (Politics of the Low Countries, 2025)
The underrepresentation of women in politics is a worldwide phenomenon and the Netherlands fit the pattern: about 39% of the Dutch MPs are female. Based on social role incongruity theory, it is expected that female politicians are evaluated more negatively than male politicians since women do not fit the dominant male politician role. However, most research is conducted in the United States, that is, a candidate-centred system where individual characteristics play an important role. This article focuses on the party-centred parliamentary context in which we examine (1) whether gender stereotypes are present among citizens and (2) to what extent these stereotypes influence the evaluation of politicians. We do this by conducting an experimental vignette survey design. We find that at the mass level there is no difference between the evaluation of male and female politicians, although gender stereotypes are present.